Rufinamide: a new antiepileptic drug treatment for Lennox-Gastaut syndrome - Ferrie, Colin D (Expert review of neurotherapeutics, 2010)
Lennox-Gastaut syndrome is a relatively rare epilepsy syndrome that usually begins in early-mid childhood and is characterized by multiple seizure types, particularly generalized seizures, which are often resistant to antiepileptic drug medication. Rufinamide is a new antiepileptic drug approved as adjunctive therapy to treat seizures in Lennox-Gastaut syndrome in those 4 years of age and older. In this article, the putative mechanism of action is described, along with data relating to its pharmacokinetics and metabolism. Key findings from clinical trials are presented and discussed. Adverse effects are summarized and compared with those encountered with competitor antiepileptic drugs. Finally, the role of rufinamide in the holistic management of subjects with Lennox-Gastaut syndrome is considered.